2019
DOI: 10.1084/jem.20190428
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and cellular age direct conversion of CD4+ T cells into RORγ+ or Helios+ colon Treg cells

Abstract: RORγ+ and Helios+ Treg cells in the colon are phenotypically and functionally distinct, but their origins and relationships are poorly understood. In monocolonized and normal mice, single-cell RNA-seq revealed sharing of TCR clonotypes between these Treg cell populations, potentially denoting a common progenitor. In a polyclonal Treg cell replacement system, naive conventional CD4+ (Tconv) cells, but not pre-existing tTregs, could differentiate into RORγ+ pTregs upon interaction with gut microbiota. A smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 79 publications
(140 reference statements)
6
44
1
Order By: Relevance
“…Our detailed cellular analysis confirms our prediction that adult thymectomy alters both Tconv and Treg composition, to somewhat similar extent, and imposes a similar bias for activated/effector/memory phenotype in the peripheral T cell pool. Our results also confirms that absence of tTreg output is not compensated by differentiation of pTreg in the periphery, as was predicted by the earlier finding that RTE are the precursors of bona fide Treg differentiated in the periphery (7,8). This finding is also consistent with the compromised return to homeostasis upon Treg perturbation, which we document in TxT animals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our detailed cellular analysis confirms our prediction that adult thymectomy alters both Tconv and Treg composition, to somewhat similar extent, and imposes a similar bias for activated/effector/memory phenotype in the peripheral T cell pool. Our results also confirms that absence of tTreg output is not compensated by differentiation of pTreg in the periphery, as was predicted by the earlier finding that RTE are the precursors of bona fide Treg differentiated in the periphery (7,8). This finding is also consistent with the compromised return to homeostasis upon Treg perturbation, which we document in TxT animals.…”
Section: Discussionsupporting
confidence: 92%
“…We extended this finding by performing adoptive transfer into lymphoreplete animals. While donor cells and newly differentiated Treg are barely detectable in lymphoreplete recipients, these are readily measurable when using DEREG recipient animals partially deleted of endogenous Treg (8). In the latter assay, as in lympho-deficient mice, cells isolated from TxT mice performed poorly ( Fig 2B).…”
Section: Functional Alteration Of Treg Upon Adult Thymectomymentioning
confidence: 96%
See 1 more Smart Citation
“…ROR‐γt + Treg are considered to be pTreg, as they do not express Helios and are induced by gut microbiota, while Helios + Treg are regarded as tTreg. However, it is debated how specific these markers are, and a recent single cell study showed that conventional T‐cells can generate both Helios + and ROR‐γt + Treg in the colon …”
Section: From Treg Classification To Foxp3 Expression Dynamicsmentioning
confidence: 99%
“…64 Furthermore, transferring LN Teffs to Treg-depleted mice, Teffs can acquire a RORct + Helios À and Helios + colonic Treg phenotype, depending on the level of nerve growth factor IB (otherwise known as Nur77). 65 Nur77 functions as an important regulator of cell survival, inflammation, but also as an early reporter for antigen-specific signalling. 66 Taken together, both tTregs and pTregs contribute to the establishment of colonic Tregs.…”
Section: Mixed Origins Of Intestinal Tregsmentioning
confidence: 99%